Analysis of The Relationship Between Customer Satisfaction and Service Quality of a Pet Shop in Depok, East Java - Tarigan, Eunike Riahta (Arthavidya Jurnal Ilmiah Ekonomi, 2020)
Abstract: In this research, the analysis gaps of customer expectation towardservice quality of a pet shop business in Depok, East Java, Indonesia by usingParasuraman’s SERVQUAL scale was investigated. The results indicatedthat all five dimensions of SERVQUAL had gaps in expectations andperformance while Reliability, Responsiveness, Assurance and Empathysignificantly gave positive gap scores (P>E). It can lead to satisfaction tocustomers, while Tangible gave a negative gap score (P<E) that affected adissatisfaction; and the customer expectations and the service performancesof the pet shop were exceeding customer expectations (P>E). Overallaverage SERVQUAL gap score was indicating satisfaction to customers. Asa quantitative research, data were collected from 50 respondents of the petshop’s customers using a questionnaire and was analyzed using SPSS. Thisresearch becomes a good input from its customers which opened anopportunity for the pet shop management to improve its businessperformance in the future.Keywords: service quality, customer expectation, service performance, petshop.